Active Commuting as a Factor of Cardiovascular Disease Prevention: A Systematic Review with Meta-Analysis - Claudia Baran; Shanice Belgacem; Mathilde Paillet; Raphael Martins de Abreu; Francisco Xavier de Araujo; Roberto Meroni; Camilo Corbellini (Journal of Functional Morphology and Kinesiology)
Active commuting (AC) may have the potential to prevent the incidence of cardiovascular disease (CVD). However, the evidence for a correlation between AC and the risk of CVD remains uncertain. The current study thoroughly and qualitatively summarized research on the relationship between AC and the risk of CVD disease. From conception through December 2022, researchers explored four databases (PubMed, PEDro, Cochrane, and Bibliothèque Nationale of Luxembourg [BnL]) for observational studies. The initial findings of the search yielded 1042 references. This systematic review includes five papers with 491,352 participants between 16 and 85 years old, with 5 to 20 years of follow-up period. The exposure variable was the mode of transportation used to commute on a typical day (walking, cycling, mixed mode, driving, or taking public transportation). The primary outcome measures were incident CVD, fatal and non-fatal (e.g., ischemic heart disease (IHD), ischemic stroke (IS), hemorrhagic stroke (HS) events, and coronary heart disease (CHD). Despite methodological variability, the current evidence supports AC as a preventive measure for the development of CVD. Future research is needed to standardize methodologies and promote policies for public health and environmental sustainability.